PRELIMINARY THERMAL CONTROL DESIGN ANALYSIS OF LAPAN SAR-MICROSATELLITE DEPLOYABLE SOLAR ARRAY PANEL USING ONE NODAL METHODE - Budiantoro, Poki Agung; Fauzi, Ahmad (Indonesian Journal of Aerospace, 2019)
LAPAN SAR-Microsatellite is the first LAPAN micro satellite being developed and planned to carry a Synthetic Aperture Radar (SAR) payload. Different from optical satellites that have been developed, LAPAN SAR-Microsatellite requires a lot more power. Solar array panels are needed to generate solar radiation into electrical energy which is used by all of subsystem satellite as energy to turn on and turn off all of components. More larger the area of solar array panel, more greater to the energy obtanied. Therefore, the needed of deployable solar array panel is a must caused by the dimension of the main body structur (MBS) are not large enough. Solar cells will experience a decrease in efficiency if they experience excessive heat. If there is a decrease in efficiency in the solar cell, it will have an impact on the decrease in power produced. The purpose of this study is to conduct thermal design on solar panels to maintain temperature according to their working temperature. Calculations are carried out on the temperature of solar array panel with various optical properties in the upper and lower panel that best which will be use using one nodal analysis methode According to the calculation result from all of the designs passive thermal control system on this study show that Design-5 is the best thermal control design which can be used for LAPAN SAR-microsatellite deployable solar array panel which α=0.24 at the top and ε=0.9 at the bottom surface of solar array panel.